The dual roles of dissimilatory iron reduction in the carbon cycle: The “iron mesh” effect can increase inorganic carbon sequestration - Cheng Zhao; Fan Xun; Biao Li; Xiaotong Han; Huan Liu; Yingxun Du; Qinglong L. Wu; Peng Xing (Global Change Biology, 2024)
Dissimilatory iron reduction (DIR) can drive the release of organic carbon (OC) as carbon dioxide (CO 2 ) by mediating electron transfer between organic compounds and microbes. However, DIR is also crucial for carbon sequestration, which can affect inorganic‐carbon redistribution via iron abiotic–phase transformation. The formation conditions of modern carbonate‐bearing iron minerals (IC Fe ) and their potential as a CO 2 sink are still unclear. A natural environment with modern IC Fe , such as karst lake sediment, could be a good analog to explore the regulation of microbial iron reduction and sequential mineral formation. We find that high porosity is conducive to electron transport and dissimilatory iron‐reducing bacteria activity, which can increase the iron reduction rate. The iron‐rich environment with high calcium and OC can form a large sediment pore structure to support rapid DIR, which is conducive to the formation and growth of IC Fe . Our results further demonstrate that the minimum DIR threshold suitable for IC Fe formation is 6.65 μmol g −1 dw day −1 . DIR is the dominant pathway (average 66.93%) of organic anaerobic mineralization, and the abiotic‐phase transformation of Fe 2+ reduces CO 2 emissions by ~41.79%. Our findings indicate that as part of the carbon cycle, DIR not only drives mineralization reactions but also traps carbon, increasing the stability of carbon sinks. Considering the wide geographic distribution of DIR and IC Fe , our findings suggest that the “iron mesh” effect may become an increasingly important vector of carbon sequestration.